Carbon Dioxide and Hemoglobin at Presentation with Hypertrophic Pyloric Stenosis—Are They Relevant? Cohort Study and Current Opinions - Ralf-Bodo Tröbs; Hiltrud Niggemann; Grigore Cernaianu; Andreas Lipphaus; Matthias Nissen (Children)
Background: Recurrent vomiting in infantile hypertrophic pyloric stenosis (IHPS) leads to metabolic alkalosis and a respiratory-driven compensatory hypercapnia. Alkalosis has been identified as the main causal factor for respiratory depression on admission. The value of contribution of hemoglobin and carbon dioxide partial pressure to this phenomenon will be evaluated. Materials and Methods: A retrospective cohort study was conducted on 105 infants with IHPS. The acid/base status, including levels of hemoglobin and lactate, were recorded. Statistical comparisons, correlation analysis, linear regression and multivariate regression analysis were applied. Results: Hypercapnia was associated with hemoconcentration. We found a positive correlation was found between pCO2 and hemoglobin (p = 0.042). The multivariate linear regression analysis showed that pCO2 is dependent on hemoglobin (p = 0.002). Lactate, which is used as a marker for anaerobic glycolysis, showed no systematic correlation with pCO2. Conclusions: An increase in carbon dioxide cannot easily be attributed to a reduced transport function of carbon dioxide due to hemoglobin deficiency. Further investigation is needed to determine the extent to which low hemoglobin levels and increased pCO2 interact with hemoconcentration to contribute to respiratory problems.